Determination of the kinetic characteristics of the heterogeneous reaction of dissociation of thebaine molecules on the surface of oxidized molybdenum - G. T. Rakhmanov; B. E. Umirzakov; Z.R. Norboyeva (Zien Journals, 2023)
Dissociative surface ionization of С19Н21О3N thebaine molecules with m/z 311 has been studied under unified conditions of nonstationary processes of surface ionization on the surface of oxidized molybdenum using unsteady methods of voltage modulation and flux modulation under unified experimental conditions.
Keywords: urface, surface ionization, adsorption, desorption, sublimation, organic compounds